Very-Short-Term Variations of Sea Surface and Atmospheric Parameters Before the Ms 6.2 Zhangbei (China) Earthquake in 1998 - Liu, Yingjia; Wu, Lixin; Qi, Yuan; Ding, Yifan (Frontiers in Environmental Science, 2022)
The Ms 6.2 Zhangbei earthquake occurred at 3:53 (UTC) on January 10, 1998, with its epicenter located 150 km about northwest to Beijing, China. Over the past two decades, many studies have reported that there was a positive thermal infrared (TIR) anomaly appearing along the direction from Bohai Sea to Zhangbei within 2 to 3 days preceding the earthquake, which was considered to be caused by the activity of the great Zhangbei-Bohai fault (ZBF) extending across the Bohai Sea to southeast, while neither the TIR anomaly is convinced nor the mechanism is clear. A collaborative analysis to the atmospheric disturbances several days before, during and after the earthquake was conducted by using satellite observations and reanalysis datasets with multiple parameters, including sea surface roughness, evaporation rate, atmospheric CO concentration, atmospheric sea salt concentration and cloud base height above sea surface, as well as satellite infrared cloud images. Through individual analysis to the change of each parameter and synergic analysis to multiple parameters, particular atmospheric disturbances including the formation of strip-shaped clouds on January 7 and 9, were revealed over the ZBF and another great fault named Tancheng-Lujiang fault (TLF), which extends across the Bohai Sea to northeast. After careful investigation and attribution analysis to the spatio-temporal evolutions of the atmospheric disturbances every hour above and around the Bohai Sea among January 7 to 12, we reached that the particular strip-shaped clouds were low-level clouds caused by the seismic activity and submarine gas release from TLF but not ZBF, and was forced by particular wind field and lowering boundary layer. As an aftereffect of the gas release from TLF and the formation of the localized low-level clouds of higher brightness temperature than that of land surface, positive TIR anomaly thus appeared above TLF and by chance along ZBF preceding the Zhangbei earthquake.